Interest-based financial system, business cycles and inclusive growth in Nigeria: an econometric analysis of the islamic perspective (2016)
Some economists are of the view that fluctuations in aggregate production in a market economy, which now appear to feature more frequently, are caused by the normal cyclical nature of the economic system comprising fluctuations of production, distribution and consumption. The real business cycle (RBC) models postulate that while real wage and the real interest rate are two prices that drive allocation process, studies on Nigeria have not extensively considered business cycles impact of interest rates despite its obvious theoretical role. Therefore, this paper attempts to provide an econometric analysis of the Islamic perspective on interest-based financial system, business cycles and inclusive growth in Nigeria. The paper deploys Vector Error Correction Model (VECM) econometric technique to Nigerian data covering 1981 to 2013 to single out the overwhelming significance of interest rates among other variables in the country’s economic fluctuations. The results from this study show that the Nigerian economy reacts negatively to any shock from the change in the interest rate and the CPI but reacts positively to the shock from the exchange rate. Due to its presence in the model, interest rate shock accounts for an average of 24 percent variability in the real GDP. Besides, the interest rate is counter-cyclical to the real GDP. The adoption of the interest-free financing mode can proffer solution to this problem.